2019
DOI: 10.3389/fimmu.2019.02333
|View full text |Cite
|
Sign up to set email alerts
|

β-Defensin 129 Attenuates Bacterial Endotoxin-Induced Inflammation and Intestinal Epithelial Cell Apoptosis

Abstract: Defensins have attracted considerable research interest worldwide because of their potential to serve as a substitute for antibiotics. In this study, we characterized a novel porcine β-defensin (pBD129) and explored its role in alleviating bacterial endotoxin-induced inflammation and intestinal epithelium atrophy. The pBD129 gene was cloned and expressed in Escherichia coli. A recombinant pBD129 protein was also purified. To explore its role in alleviating the endotoxin-induced inflammation, mice, with or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…For example, fowlicidin-1 can neutralize bacterial lipopolysaccharide (LPS) 28 , a microbe-associated molecular pattern that potently induces inflammation 29 . Furthermore, beta-defensins reduce intestinal apoptotic signals in LPS-treated animals 30 . Thus, improving the production of these AMPs may both increase resistance against bacterial pathogens, as well as mitigate host damage induced by these antibacterial responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fowlicidin-1 can neutralize bacterial lipopolysaccharide (LPS) 28 , a microbe-associated molecular pattern that potently induces inflammation 29 . Furthermore, beta-defensins reduce intestinal apoptotic signals in LPS-treated animals 30 . Thus, improving the production of these AMPs may both increase resistance against bacterial pathogens, as well as mitigate host damage induced by these antibacterial responses.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al [ 40 ] evaluated the preventive action of pig β-defensin 129 (pBD129) in mice that received intraperitoneal LPS. The results showed that this β-defensin also attenuated the inflammatory response and mucosal atrophy by reducing the secretion of inflammatory cytokines and the apoptosis of intestinal epithelial cells, which indicates antibacterial and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…As regards viable alternatives to antibiotics, defensins have been reported to have effective antimicrobial activities against infectious agents, including bacteria. Within the 29 porcine β-defensins discovered so far, the antibacterial activities of porcine β-defensin 1, PBD-2, and porcine β-defensin 129 have been well described [ 6 , 38 , 39 ]. Notably, since the discovery of PBD-2 in 2006 via sequence similarity analysis [ 40 ], PBD-2 has been the most studied porcine defensin regarding its antibacterial property.…”
Section: Discussionmentioning
confidence: 99%